Kultura szkoły – wyzwanie dla włączającego kształcenia - Chrzanowska, Iwona (Pedagogika Społeczna Nova, 2021)
The article focuses on the issues of inclusive education and school culture. The main aim of the article is to introduce the concept of inclusive education and to reflect on the meaning of building the orga- nizational culture of school for the shaping of educational paths of students with disabilities and their functioning in peer relations. The literature analysis clearly shows that a large percentage of students with disabilities (approx. 30%) change their first-choice school (mainstream) to another one during their education. The data showing a low position of a student with a disability in the classroom are disturbing. It seems that building the organizational culture of an inclusive school will be an important factor of positive change in this case. Basing it on values, norms and standards of practice that, as internalized beliefs and attitudes of the entire school community (staff, students and parents) will create conditions for the individual and social development of all students.